Recent advances in software tools for adsorption science and engineering. Issue 7 (7th June 2022) - Ga, Seongbin; Chung, Yongchul G.
Abstract : We provide overviews of recent developments in the software tools for both molecular and process simulations for adsorption science and engineering. Abstract : Adsorption processes are widely regarded in the literature as an energy-efficient alternative to more traditional separation methods, such as absorption and distillation. The key to adsorption-based separation is in the adsorbent materials and adsorption process operation. Despite its importance, a relatively small number of studies have been published in the literature to review the current state-of-the-art of adsorption process modeling, especially in the context of multi-scale modelling. In this review, we discuss the current state-of-the-art of adsorption process modeling, with the focus on software tool developments. Several technical simplifications and advances commonly employed in software development are discussed along with their advantages and limitations.